Electronic and optical properties of InAs/InAs0.625Sb0.375 superlattices and their application for far-infrared detectors. (8th December 2022) - Hussain, Ghulam; Cuono, Giuseppe; Islam, Rajibul; Trajnerowicz, Artur; Jureńczyk, Jarosław; Autieri, Carmine; Dietl, Tomasz
Abstract: We calculate the electronic and optical properties of InAs/InAs0.625 Sb0.375 superlattices (SLs) within relativistic density functional theory. To have a good description of the electronic and optical properties, the modified Becke–Johnson exchange-correlation functional is employed to describe the band gaps correctly. First, we analyze the electronic and optical characteristics of bulk InAs and InSb, and then we investigate the InAs/InAs0.625 Sb0.375 SL. The optical gaps deduced from the imaginary part of the dielectric function are associated with the characteristic interband transitions. We investigate the electronic and optical properties of the InAs/InAs0.625 Sb0.375 SL with three lattice constants of the bulk InAs, GaSb and AlSb, respectively. It is observed that the electronic and optical properties strongly depend on the lattice constant. Our results support the presence of two heavy-hole bands with increasing in-plane effective mass as we go far from the Fermi level. We notice a considerable decrease in the energy gaps and the effective masses of the heavy-holes in the k x – k y plane compared to the bulk phases of the parent compounds. We demonstrate that the electrons are s -orbitals delocalized in the entire SL, while the holes have mainly p -Sb character localized in the In(As, Sb) side of the SL. In the SL, the low-frequency absorption spectra greatly increase when the electric field is polarized orthogonal to the growth axis allowing the applicability of III–V compounds for the long-wavelength infrared detectors.